Relationship History of Parenting and Antenatal Care Visits with Stunting Events in Children Aged 24-36 Months in West Aceh Regency - Cut Hartati; Etti Sudaryati; Fikarwin Zuska (Randwick International of Social Science Journal, 2024)
Stunting is the inability of children under five to grow normally due to the effects of chronic lack of nutrition so that their height is very short for their age. Data from SSGI in 2022, Aceh Province has a prevalence rate of stunting among children under five which is ranked fifth with a percentage of 31.2 percent. According to SSGI data for 2021, stunting in West Aceh Regency was 27.4 percent and increased to 30.4 percent in 2022 with a very high category. The aim of this research is to analyze the relationship between parenting styles and the incidence of stunting in children 24-36 months in West Aceh Regency. This type of research is quantitative research with a case control design. The sample size was 100 toddlers, 50 toddlers were selected for the case group and 100 toddlers for the control group. The results of the study showed that the variables that were related were parenting patterns for breastfeeding and food (p=0.016), personal hygiene parenting patterns (p=0.028) and history of antenatal care visits (p=0.007) with the incidence of stunting. Suggestions for this research to the government are expected to be able to synergize better in creating programs to overcome stunting and poverty and improve the performance of services and implementation of specific nutritional intervention programs for pregnant women. One of them is an examination program during pregnancy both in terms of quantity of visits and also inspections carried out during ANC activities.